1991
DOI: 10.1037/0022-3514.61.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depression on quantity and quality of social inferences.

Abstract: Two studies explored depressives' sensitivity to social information as an impediment to their gaining a sense of confidence and control. In Study 1, Ss viewed a videotape of an actor performing an achievement task and were asked to list their impressions of the actor. As compared with nondepressed Ss, depressed Ss generated more inferences overall, generated more abstract inferences, and exhibited less overall confidence in their impression of the actor. In Study 2, Ss reported their beliefs of the utility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 30 publications
4
73
0
Order By: Relevance
“…In particular, the existing evidence (from studies of older children, adolescents, and adults) highlights the complexity of relations between mind-reading skills and different types of internalizing problems. For example, individual differences in mental state awareness/reasoning have been reported as showing positive associations with dysphoria (Gleicher & Weary, 1991;Harkness, Sabbagh, Jacobson, Chowdrey, & Chen, 2005;Marsh & Weary, 1989) but as showing negative associations with anxiety problems (Banerjee, 2008;Banerjee & Henderson, 2001;Harkness et al, 2005) and with bipolar affective disorder (e.g., Kerr, Dunbar, & Bentall, 2003;Schenkel, Marlow-O'Connor, Moss, Sweeney, & Pavuluri, 2008). Therefore, there is mixed support for the idea that good mindreading may come at a cost to the individual.…”
Section: Conclusion and Caveatsmentioning
confidence: 91%
“…In particular, the existing evidence (from studies of older children, adolescents, and adults) highlights the complexity of relations between mind-reading skills and different types of internalizing problems. For example, individual differences in mental state awareness/reasoning have been reported as showing positive associations with dysphoria (Gleicher & Weary, 1991;Harkness, Sabbagh, Jacobson, Chowdrey, & Chen, 2005;Marsh & Weary, 1989) but as showing negative associations with anxiety problems (Banerjee, 2008;Banerjee & Henderson, 2001;Harkness et al, 2005) and with bipolar affective disorder (e.g., Kerr, Dunbar, & Bentall, 2003;Schenkel, Marlow-O'Connor, Moss, Sweeney, & Pavuluri, 2008). Therefore, there is mixed support for the idea that good mindreading may come at a cost to the individual.…”
Section: Conclusion and Caveatsmentioning
confidence: 91%
“…For instance, Isen and Means (1983) found that people induced to feel happy were better at performing a complex mental task-namely, eliminating unimportant information and discovering useful heuristics to help solve a difficult problem. Sad individuals, in contrast, are more likely to ignore heuristic shortcuts and to use effortful, vigilant processing even when it is not required, and therefore perform poorly in complex and timelimited situations (Gleicher & Weary, 1991). For example, in a recent study, sad participants displayed reduced accuracy of social judgments based on thin slices of nonverbal behavior (Ambady & Gray, 2002).…”
Section: Performance On Complex Mental Tasksmentioning
confidence: 99%
“…It looks for evidence of three possible response patterns. The first is that sadness triggers more causal attributions than does anger, due to the heightened level of active, deliberate processing associated with sadness (Alloy & Abramson, 1979;Ambady & Gray, 2002;Bodenhausen, 2000;Bodenhausen et al, 1994;Gleicher & Weary, 1991;Wenzlaff et al, 1988). The second, and contradictory, pattern is that sadness creates fewer causal attributions than anger, because anger arises from and gives rise to appraisals of justice and blame (Lazarus, 1991;Lerner et al, 1998).…”
Section: Synthesis Of Present Study and Hypothesesmentioning
confidence: 99%
“…Sadness and anger have been studied, however, in other relevant aspects of social information processing. For example, sadness triggers active, deliberative thought (Alloy & Abramson, 1979;Ambady & Gray, 2002;Bodenhausen, Gabriel, & Lineberger, 2000;Gleicher & Weary, 1991;Wenzlaff, Wegner, & Roper, 1988), whereas anger triggers relatively heuristic thought (Lerner, Goldberg, & Tetlock, 1998;Tiedens & Linton, 2001). In a direct comparison of these two negative emotions, sad people used more systematic, detail-oriented strategies than did angry people, including relying less on stereotypes and other heuristic cues (Bodenhausen, Sheppard, & Kramer, 1994).…”
mentioning
confidence: 99%